Indonesian Food Translation Approaches Found in 5-Star Hotel Restaurant Menus in Bali - Kencana, Ni Putu Rena Wahyu; Kuntayuni; Pratama, Agus Darma Yoga (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This research investigated the translation strategies used to translate Indonesian food menus into English at 5-star hotel restaurants in Bali. It also explored the use of cultural-specific items (CSIs) in these translations. The study employed a qualitative research method, gathering data from the official websites of six different 5-star restaurants in Bali. The primary theoretical framework was Beekman and Callow's